Predictors of apical periodontitis in root canal treated teeth from an adult Nepalese subpopulation: a cross-sectional study - Md. Asdaq Hussain; Shailendra Kumar Singh; Shazia Naz; Merazul Haque; Harish Kumar Shah; Abanish Singh (BMC, 2024)
Abstract Background Endodontic literature search revealed that no study has been conducted to evaluate the prevalence of apical periodontitis (AP) in root canal treated teeth from an adult Nepalese population of Madhesh Province. Consequently, little is known about the extent and risk factors associated with it. This study aimed to determine AP prevalence in root canal treated teeth from an adult Nepalese subpopulation and to analyze the related risk factors including age, sex, tooth type, type of coronal restoration and quality of root canal treatment and coronal restoration as predictors of AP. Methods Digital panoramic radiographs were evaluated. Periapical status of 300 root canal-treated teeth was scored by using the periapical index. The quality of root canal treatment and coronal restorations were categorized as adequate or inadequate through radiographic and clinical evaluation. The data were analyzed using univariate and multivariate logistic regression models. Results Prevalence of AP in the present study was 31.7%. In 45.7% of the treated teeth, quality of root canal treatment was adequate whereas 46% of the cases had adequate coronal restorations. Multivariate logistic regression analysis revealed statistically significant associations and remarkably increased risk for AP in teeth with inadequate root canal treatment (odds ratio [OR] = 7.92; 95% CI: 3.96-15.82; p < 0.001) whereas lower risk for AP was found in females (OR = 0.51; 95% CI: 0.28-0.90; p = 0.021) and in teeth restored with crown (OR = 0.22; 95% CI: 0.09-0.51; p < 0.001) and filling (OR = 0.18; 95% CI: 0.08-0.42; p < 0.001). Quality of coronal restoration, tooth type and age of the patient were not found to be the predictors of AP. Conclusions Within the limits of this study, a high prevalence of AP and poor overall quality of root canal treatment and coronal restoration was found in the subpopulation studied. Quality of root canal treatment, type of coronal restoration and sex of the patient are significant predictors of possible AP development in root canal treated teeth. Substantial efforts are needed to improve the endodontic treatment standards.